Interpersonal Communication Between Parents-Children in Increasing Children's Protection from Cyberbullying - Mirdan Kurniawan; Rosy Febriani Daud; Sa’adatul Madiniah (PT ARRUS Intelektual Indonesia, 2023)
In this digital era, children are very vulnerable to being exposed to the risks and dangers of technological developments, especially social media. Such as inappropriate content, online violence, cyber bullying, and many other impacts of technology and media. For this reason, it is important for parents to increase their children's protection from media exposure and the influence of technology in this digital era. Therefore, interpersonal communication between parents and children must be improved to protect children from the bad influences of media and technology. Parents need to improve good communication with their children so that they are willing to tell stories and share experiences about the problems they are facing, so that children feel comfortable and have a place to share their stories. Apart from that, parents also need to provide education regarding technology and its impacts and know the risks they will face, so that children can be more efective and wise in dealing with technological developments. The way that can be done is to provide adequate supervision and limit children's excessive use of media, so as to minimize the impact they will receive. This research article aims to determine interpersonal communication between parents and children so that it is effective and can increase protection for children from developments in digital technology such as cyberbullying. This research article uses qualitative methods with descriptive data processing techniques.